Pelatihan Pembuatan Modul Ajar Berbasis Deep Learning bagi Guru SD di Kota Atambua - Silvester P Taneo; Maxsel Koro; Adam Bol Nifu Benu (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The digital transformation in education requires teachers to adapt technology-based learning approaches, one of which is deep learning. Deep learning, as a pedagogical approach, not only reflects advances in artificial intelligence technology but also represents a new paradigm in immersive learning that emphasizes active, reflective, and student-centered engagement. However, many elementary school teachers in border areas, such as Atambua City, still encounter challenges in designing teaching modules based on this approach. Therefore, this community service activity aims to provide training in the development of deep learning-based teaching modules to elementary school teachers in Atambua City. The implementation method included needs identification, workshops, hands-on practice, mentoring, and evaluation. The results of the activity showed a significant increase in the understanding of deep learning concepts and the ability of teachers to develop contextual and innovative teaching modules. Teachers also demonstrated high enthusiasm in implementing the training outcomes in their classrooms. This training had a positive impact on the quality of lesson planning, which focuses on developing critical thinking skills, collaboration, and student creativity. This activity is recommended for replication in other regions, especially those that are lagging behind in the use of technology-based learning approaches.